Utilization of Crossword Puzzle Media Based on The Puzzle Maker Application As An Evaluation Tool for Learning Islamic Religious Education - Permata Intang (IAIN Parepare, 2024)
The main problem faced in learning at SMK DDI Parepare is the low motivation and involvement of students in the evaluation process of Islamic Religious Education (PAI). To overcome this, this study aims to evaluate the effectiveness of using crossword puzzle media based on the Puzzle Maker application as an evaluation tool for PAI learning in class XI. This media is expected to increase student participation and learning outcomes through more interesting interactions. This study uses a qualitative descriptive method with a field study approach. Data were collected through in-depth interviews, observations, and documentation. Data analysis was carried out in three stages, namely data reduction, data presentation, and drawing conclusions. Data validity testing used triangulation. The subjects of the study consisted of PAI teachers and class XI students at SMK DDI Parepare. The results of the study showed that the use of crossword puzzle media based on the Puzzle Maker application can increase student participation in the PAI learning evaluation process. Students are more enthusiastic and motivated to participate in the evaluation because of the challenging game elements. In addition, the use of this technology makes it easier for teachers to prepare evaluation questions effectively. However, technical constraints such as the availability of LCD projector devices are still a challenge. Overall, this media provides a positive response from both teachers and students in implementing learning evaluations.